2020
DOI: 10.1002/etc.4848
|View full text |Cite
|
Sign up to set email alerts
|

The Spider Exposure Pathway and the Potential Risk to Arachnivorous Birds

Abstract: There is growing concern over the health of North American birds, with evidence suggesting substantial population declines. Spiders are prominent dietary items for many bird species and mediate the transfer of contaminants to arachnivorous birds that consume them. Few studies have investigated the potential risk the spider exposure pathway poses to these birds because most studies have focused on piscivores. In the present study, we developed new chronic and acute As, Cd, Cu, Pb, Ni, Se, Zn, and MeHg spider-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…The retention or bioaccumulation of Hg, PCBs, and Se in the tissues of riparian spiders has been demonstrated repeatedly (Table 1). The algal toxin microcystin (Moy et al, 2016), organic contaminants including per‐ and polyfluoroalkyl substances (PFAS), along with several pharmaceuticals and endocrine‐disrupting compounds (Koch et al, 2020; Previšić et al, 2021; Richmond et al, 2018), and some metals including Cd, Cu, Cr, Zn, and Pb have been less well studied but have been found to be retained in the tissues of riparian spiders (Beaubien et al, 2020; Cetinić et al, 2021; Du Laing et al, 2002; Hendrickx et al, 2004; Kim & Kim, 2016; Kraus et al, 2021; Maelfait & Hendrickx, 1998; Otter et al, 2013; Ramirez et al, 2011; Schipper et al, 2008; Tojal et al, 2002; Torres & Johnson, 2001; Zhang et al, 2009). This suggests that riparian spiders may be suitable sentinels for these contaminants as well (but see Cetinić et al, 2021; Kim & Kim, 2016; Kraus et al, 2021; Torres & Johnson, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The retention or bioaccumulation of Hg, PCBs, and Se in the tissues of riparian spiders has been demonstrated repeatedly (Table 1). The algal toxin microcystin (Moy et al, 2016), organic contaminants including per‐ and polyfluoroalkyl substances (PFAS), along with several pharmaceuticals and endocrine‐disrupting compounds (Koch et al, 2020; Previšić et al, 2021; Richmond et al, 2018), and some metals including Cd, Cu, Cr, Zn, and Pb have been less well studied but have been found to be retained in the tissues of riparian spiders (Beaubien et al, 2020; Cetinić et al, 2021; Du Laing et al, 2002; Hendrickx et al, 2004; Kim & Kim, 2016; Kraus et al, 2021; Maelfait & Hendrickx, 1998; Otter et al, 2013; Ramirez et al, 2011; Schipper et al, 2008; Tojal et al, 2002; Torres & Johnson, 2001; Zhang et al, 2009). This suggests that riparian spiders may be suitable sentinels for these contaminants as well (but see Cetinić et al, 2021; Kim & Kim, 2016; Kraus et al, 2021; Torres & Johnson, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies have statistically assessed taxonomic differences in contaminant concentrations (Abeysinghe et al, 2017; Bartrons et al, 2015; Beaubien et al, 2020; Hannappel et al, 2021; Hendrickx et al, 2004; Kraus et al, 2017; Ortega‐Rodriguez et al, 2019; Sullivan et al, 2016; Tavshunsky et al, 2017; Tojal et al, 2002; Walters et al, 2008, 2010; Walters et al, 2018). Among these, more than 80% (10 out of 12 studies) reported taxonomic differences in contaminant accumulation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations